Indoor fungal diversity in primary schools may differently influence allergic sensitization and asthma in children - Cavaleiro Rufo, João (2018)
Childhood exposure to microbiologic agents may influence the development of allergic and respiratory diseases. Apart from home, children spend most of their time at school, which represents an environment of significant exposure to indoor air microbes. Therefore, we aimed to assess how the prevalence of allergic sensitization and asthma in schoolchildren is affected by microbiologic exposure within classrooms.